2005
DOI: 10.1002/ddr.20057
|View full text |Cite
|
Sign up to set email alerts
|

The effect of estrogens and antiestrogens in rat models of hot flush

Abstract: Rat models of hot flush provide important preclinical tools for evaluating the effect of estrogens and the selective estrogen receptor modulators (SERM), including tamoxifen, raloxifene, and tibolone, some of which have received renewed attention as agents to treat neurodegenerative diseases. The first rat model of hot flush is the ovariectomized morphine-dependent model. When morphine is withdrawn with the opioid antagonist naloxone, temperature of the tail is increased by 4-61C (''hot flush''). Estrogens red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…EE treatment at this high dose (1 mg/kg body weight), on the other hand, produced an approximate 50% decrease in TST increase at this time point compared to the control group upon Nlx challenge, while an approximate 25% decrease was observed in this measure with the significantly lower dose of prodrug (300 µg/kg body weight, p.o.). Although these changes were less than what we observed by using OVX rats [17,[25][26][27] and required a 5 to 10 times higher EE dose to observe attenuation of the effect caused by morphine withdrawal, nevertheless it represented discernible decreases in TST in relation to the no drug treatment. We also found that areas under the TST-time curves (AUCs) were more reliable to assess the effect of the drug treatment than temperature recorded at a somewhat arbitrarily preselected time point such as 15 min after the injection of Nlx.…”
Section: Dhed Treatment Blunted Increase Of Tst In Ordx Male Rats In contrasting
confidence: 75%
See 4 more Smart Citations
“…EE treatment at this high dose (1 mg/kg body weight), on the other hand, produced an approximate 50% decrease in TST increase at this time point compared to the control group upon Nlx challenge, while an approximate 25% decrease was observed in this measure with the significantly lower dose of prodrug (300 µg/kg body weight, p.o.). Although these changes were less than what we observed by using OVX rats [17,[25][26][27] and required a 5 to 10 times higher EE dose to observe attenuation of the effect caused by morphine withdrawal, nevertheless it represented discernible decreases in TST in relation to the no drug treatment. We also found that areas under the TST-time curves (AUCs) were more reliable to assess the effect of the drug treatment than temperature recorded at a somewhat arbitrarily preselected time point such as 15 min after the injection of Nlx.…”
Section: Dhed Treatment Blunted Increase Of Tst In Ordx Male Rats In contrasting
confidence: 75%
“…We have previously described the pharmacological hot flush model adopted for the purpose of drug discovery and early phase development using OVX rats [16,17,25,27]. To our knowledge, this is, however, the first report involving ORDX rats in this context (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations